The interstellar medium properties of heavily reddened quasarsand companions at z∼ 2.5 with ALMA and JVLA. Issue 1 (2nd June 2018) - Banerji, Manda; Jones, Gareth C; Wagg, Jeff; Carilli, Chris L; Bisbas, Thomas G; Hewett, Paul C
ABSTRACT: We study the interstellar medium (ISM) properties of three heavily reddened quasars at z ∼ 2.5 and three millimetre-bright companion galaxies near these quasars. New Karl G. Jansky Very Large Array (JVLA) and Atacama Large Millimeter Array (ALMA) observations constrain the CO(1–0), CO(7–6), and [CI] 3 P2 − 3 P1 line emission and the far-infrared to radio continuum. The gas excitation and physical properties of the ISM are constrained by comparing our observations to photodissociation region models. The ISM in our high-redshift quasars is composed of very high-density, high-temperature gas that is already highly enriched in elements like carbon. One of our quasar hosts is shown to be a close-separation (<2 arcsec) major merger with different line emission properties in the millimetre-bright galaxy and quasar components. Low angular resolution observations of high-redshift quasars used to assess quasar excitation properties should therefore be interpreted with caution as they could potentially be averaging over multiple components with different ISM conditions. Our quasars and their companion galaxies show a range of CO excitation properties spanning the full extent from starburst-like to quasar-like spectral line energy distributions. We compare gas masses based on CO, CI, and dust emission, and find that these can disagree when standard assumptions are made regarding the values of α CO, the gas-to-dust ratio, and the atomic carbon abundances. We conclude that the ISM properties of our quasars and their companion galaxies are diverse and likely vary spatially across the full extent of these complex merging systems.